Reactions of Calcium Phosphate and Calcium Oxalate with Kurthi (Dolichos bifluorus) Extract (Fresh and Hydrolysed) - Mahapatra (Chowdhury), Basabi; Bala, Shahil (Asian Journal of Chemistry, 2010)
An attempt has been made to study the reactivity of Kurthi (Dolichos bifluorus) on urinary stones as natural polyphosphates have never been harnessed for their value in the dissolution of urinary stones.